2020
DOI: 10.1021/jacs.0c06618
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Regulation of Multivalent Terpyridine Ligands for Self-Assembly of Heteroleptic Metallo-Supramolecules

Abstract: A two-ligand system composed of the predesigned multivalent and complementary terpyridine-based ligands was exploited to construct heteroleptic metallo-supramolecules and to investigate the self-assembly mechanism. Molecular stellation of the trimeric hexagon [Cd6 L 2 3] gave rise to the exclusive self-assembly of the star hexagon [Cd18 L 1 6 L 3 3] through complementary ligand pairing between the ditopic and octatopic tectons. To understand how the intermolecular heteroleptic complexation influenced the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…110 By further complicating the structure of the ligands, a variety of integrative social self-sorting patterns were easily fabricated. Chan et al reported a series of terpyridine based multi-armed ligands that assembled with Cd 2+ into nanocapsules, 111 starlike structures, 28 triangles or hexagons. 111 Other structures like snowflake 112 and cage 83,113 were also achieved by varying the structure of ligands.…”
Section: Spatial Arrangementmentioning
confidence: 99%
“…110 By further complicating the structure of the ligands, a variety of integrative social self-sorting patterns were easily fabricated. Chan et al reported a series of terpyridine based multi-armed ligands that assembled with Cd 2+ into nanocapsules, 111 starlike structures, 28 triangles or hexagons. 111 Other structures like snowflake 112 and cage 83,113 were also achieved by varying the structure of ligands.…”
Section: Spatial Arrangementmentioning
confidence: 99%
“…Recently IMS-MS has not only characterized occluded CDSA products, such as constitutional isomers and configurational isomers ( Ujma et al, 2012 ; Schultz et al, 2013 ; Liang et al, 2015 ), but also the “erroneous” intermediates formed in multicomponent systems ( Wang et al, 2020c ), or impressively, the lack thereof in a multicomponent system, due to successful pre-organization ( Wang et al, 2020a ), and even the formation of pre-organized “sequenced” CDSA systems ( Song et al, 2018 ). As such, the structural analysis of CDSA systems using IMS-MS ultimately leads us beyond characterisation of the product and side products, and towards an understanding of CDSA mechanisms.…”
Section: Applications Of Ion Mobility Mass Spectrometry To Study Coordination Driven Self-assemblymentioning
confidence: 99%
“…Self-sorting is an intrinsically difficult behaviour to interrogate, more so than self-assembly alone, because all the potential supramolecular assemblies will be formed from the same source molecules, leading to similar sets of signals. IMS-MS is again uniquely situated to differentiate between self-sorted complexes that may otherwise appear similar by other techniques ( Liang et al, 2015 ; Wang et al, 2020c ). For example, TIMS-MS succeeded in differentiating between heteroleptic cages where DOSY NMR could not, however these cages were statistical products, not self-sorted ( Ebbert et al, 2019 ).…”
Section: Applications Of Ion Mobility Mass Spectrometry To Study Coordination Driven Self-assemblymentioning
confidence: 99%
“…2,2':6',2''-terpyridine (tpy) derivatives have been widely used to construct numerous novel supramolecular structures [54][55][56][57][58][59] with special functions, including catalysis, 60,61 medicine, 62 sensing, 63,64 smart materials, 65,66 and optoelectronic devices. [67][68][69] However, the octahedral coordination geometry of the tpy-M(II)-tpy complex can cause significant steric hindrance, which limits the application in the formation of mechanically interlocked structures based on coordination-directed instead of templating.…”
Section: Introductionmentioning
confidence: 99%